Estimating the Black Hole Spin for the X-Ray Binary MAXI J1727-203 Based on Insight-HXMT - Haifan Zhu; Wei Wang (The Astrophysical Journal)
We constrain the spin of the black hole candidate MAXI J1727-203 using Insight-HXMT data. Due to limited Insight-HXMT observations covering only part of the outburst, NICER data were used to analyze the full outburst’s state transitions; we identified two of three HXMT observations in the high soft state and applied the continuum-fitting method to measure the spin. Based on previous estimates and continuum spectral fittings, we explored the parameter space and found that the best-fitting values were ( D , i , M ) ≈ (6 kpc, 30°, 12 M _⊙ ). We also tested the variation of these parameters using Monte Carlo simulations, sampling over 3000 sets within the parameter ranges 5.9 kpc <  D  < 7 kpc, 24° <  i  < 35°, and 10 M _⊙ < M < 14 M _⊙ , yielding a spin measurement of $a=0.3{4}_{-0.19}^{+0.15}$ (1 σ ). In addition, we analyzed NuSTAR data in the low hard state and found a good fit with the tbabs∗(diskbb+powerlaw) model, with no significant iron line features observed in the residuals; therefore, the previous reflection model results suggesting an extremely high spin overestimates the black hole spin.